Bio‐based benzoxazines synthesized in a deep eutectic solvent: A greener approach toward vesicular nanosystems. (2nd January 2020) - Behalo, Mohamed S.; Bloise, Ermelinda; Mele, Giuseppe; Salomone, Antonio; Messa, Francesco; Carbone, Luigi; Mazzetto, Selma Elaine; Lomonaco, Diego
Abstract: A green synthesis of benzoxazines, based upon reaction of cardanol with formaldehyde and primary amines, is achieved in high yields using choline chloride‐urea mixture as deep eutectic solvent. Then, it is demonstrated how the cardanol‐based benxoxazines can be employed as only component for the preparation of a nanovesicular systems. Abstract :